Genetic algorithms for finding episodes in temporal networks - Castelli, Mauro (2021)
Castelli, M., Dondi, R., & Hosseinzadeh, M. M. (2020). Genetic algorithms for finding episodes in temporal networks. Procedia Computer Science, 176, 215-224. https://doi.org/10.1016/j.procs.2020.08.023